Tajikistan’s business sector for years of independence: problems and development models - A. A. Urunov; I. M. Morozova; K. K. Zoidov; M. G. Mansurova (Вестник университета)
The purpose of the study is to develop strategic priorities for the development of the business sector of Tajikistan based on the analysis of the structure of the economy of the republic and its dynamics, as well as the use of economic and mathematical modeling of the object under study. The article identifies the main obstacles to the development of the business sector, including: inefficient functioning of management institutions and the market; insufficient development of human capital; underdeveloped industrial and social infrastructure, as well as the legal framework governing the relations of the state, business, labor, etc. Based on the use of statistical methods of analysis, in particular the method of principal components, two important strategic vectors of development of the business sector aimed at economic diversification have been identified. The first direction involves the development of industry and construction with the participation of the state in the form of public-private partnership, increasing the production of import-substituting goods based on its own resources. The second direction should be the modernization of social and industrial infrastructure, including energy. The measures aimed at improving the business climate, overcoming regional and sectoral fragmentation of the economy of Tajikistan, ensuring its sustainable and balanced development are proposed. The results of the study can be used in the development of the state strategy for the development of entrepreneurship in the Republic of Tajikistan, as well as in the process of state regulation of spatial development.